THE JURIDICAL APPROACH IN INDONESIA COMPETITION LAW - Retno Tri Rahayu; Ria Setyawati (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
Implementation of juridical approach which is per se illegal or rule of reason is not easy to apply in cases of business competition. It can be seen from the violation case of article 27 of Law No. 5 of 1999 regarding the case of Cinema 21 which was decided using the Perse Illegal approach. However, in the same case concerning the cross ownership of the Temasek Group case, the Business Competition Supervisory Commission decides to use the Rule of Reason approach. In order to avoid uncertainty arising from the differences in the use of juridical approach, then this study reviews the juridical accuracy towards the cross ownership in the legal perspective of business competition. After analyzing several aspect considerations, it could be concluded that the Rule of reason approach was more accurate to apply because it could prove the fulfillment of the elements in article 27.